Hepatocellular Carcinoma: Cause of Diaphragmatic Herniation in Canine - Kumar, Sarvan; Tiwari, Vipin; Sakshi; Choudhary, Anju; Mandal, Kruti D. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Diaphragmatic hernia (DH) may be congenital or acquired. Most diaphragmatic defects reported in bovines are either traumatic in origin or have a history of advanced pregnancy or recent calving (Smith, 2002). DH may also occur as a result of progressive weakening of the diaphragm adjacent to a hardware perforation and reticuloperitonitis (Divers and Peek, 2008). There is meager literature on congenital diaphragmatic defects in horses and accidental, spontaneous rupture usually occurs from abdominal crushing, following blunt trauma or penetrating injuries to the abdomen and chest (Sasho and Dian, 2009). Cases of DH in canine are less frequently noticed. There is the occasional report of DH in canines due to a neoplastic growth like hepatocellular carcinoma. This communication reports a case of Rottweiler pup, which was presented with clinical signs of dyspnea and vomiting, that was tentative diagnosed as respiratory pathology and was subjected to further investigation and autopsy.